2020
DOI: 10.1158/0008-5472.can-19-3067
|View full text |Cite
|
Sign up to set email alerts
|

A Protease-Activated Fluorescent Probe Allows Rapid Visualization of Keratinocyte Carcinoma during Excision

Abstract: are co-founders, and Brian Straight is the CEO of Akrotome Imaging, Inc. Daniel Popkin is a scientific advisory board member for Akrotome Imaging, Inc. No potential conflicts of interest are disclosed by the other authors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 67 publications
(73 reference statements)
1
9
0
Order By: Relevance
“…Testing of gel#30 using a human lumpectomy sample showed a strong, robust, and specific ICG signal at the area of BCa ( Figure 6 ). This single application of AKRO-QC-ICG imaging gel in its current formulation fully corroborates our previous clinical studies [ 30 , 31 , 49 ] and builds a strong case to support the clinical merit of topical application of imaging probes as an approach to optically visualize cancer tissue both ex vivo and in vivo. Most recently, de Jongh et al [ 56 ] reported on the discrepancy between true negative margins and those obtained after using IV-administered FIGS.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Testing of gel#30 using a human lumpectomy sample showed a strong, robust, and specific ICG signal at the area of BCa ( Figure 6 ). This single application of AKRO-QC-ICG imaging gel in its current formulation fully corroborates our previous clinical studies [ 30 , 31 , 49 ] and builds a strong case to support the clinical merit of topical application of imaging probes as an approach to optically visualize cancer tissue both ex vivo and in vivo. Most recently, de Jongh et al [ 56 ] reported on the discrepancy between true negative margins and those obtained after using IV-administered FIGS.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, fluorescent SBPs can be rendered optically silent by the addition of a quenching moiety that is lost upon reaction with the protease target of interest, ensuring that the probes only produce a signal in tumor tissue when acted upon by an enzyme activity associated with a tumor or its surrounding margins [ 47 ]. In our more recent work, we have developed a method for topical application of imaging probes to tissues using topical application of both quenched activity-based probes [ 28 , 29 , 48 ] and a third generation quenched SBP [ 31 , 49 ]. Topical application into the surgical cavity to identify remaining or “missed” cancer following lumpectomy has the potential to reduce positive surgical margins and integrates well into the surgical workflow.…”
Section: Introductionmentioning
confidence: 99%
“…Given this degree of posttranslational regulation, quantifying protease activity, rather than transcriptomic or proteomic analyses, is often required to understand the biological roles of proteases 5 . This has motivated the development of activity-based sensorsprobes that quantify protease activitywhich are used for early detection of disease [6][7][8][9][10][11] , biological imaging [12][13][14] , and drug screening 15,16 . The two primary compositions of activity-based sensors are (1) substrates that produce a signal upon proteolysis and (2) probes that bind active proteases 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of the technique is due to the preliminary sample processing that may not be fully reproducible. Many methods using fluorescent dyes injected into the patient or incubated with the tissue specimen are under development [13][14][15][16][17][18], showing high sensitivity and specificity but restricted to surface imaging with low tissue penetration and requiring a long process for the identification and authorisation of the proper candidate for a given tumour. Quantitative micro-elastography (QME) is an emerging technique that produces images of tissue microscale elasticity and has also been recently proposed for margin assessment in cancers that are known to exhibit altered mechanical properties [19], but the difficult interpretation of the images obtained remains the main drawback for this technology.…”
Section: Introductionmentioning
confidence: 99%